Towards a Circular Economy: A Systematic Review of Business Model Innovation in the Age of Sustainability - Yudhistira Ardana (Generate Digital Publishing, 2025)
Objectives: This study aims to synthesize recent developments in business model innovation (BMI) and its strategic role in accelerating the transition toward a circular economy and comprehensive sustainability practices. It specifically examines how different innovation dimensions digital, social, organizational, and bio based shape sustainable and circular business models, while highlighting critical pathways to strengthen systemic collaboration across key stakeholders. Research Design & Methods: The study employs a systematic literature review, analyzing peer-reviewed publications from 2019 to 2024. A thematic analysis technique was used to classify innovation types, assess their contributions to sustainability and circular outcomes, and identify emerging research gaps and directions. Findings: BMI serves as a core enabler of sustainable transformation. Digital innovation enhances transparency, real-time environmental monitoring, and process optimization. Social innovation amplifies user participation and fosters collaborative, community-based solutions. Organizational innovation institutionalizes sustainable values through policy reforms, culture change, and structural adaptation. In circular business contexts, bioeconomy innovation leverages renewable biological resources, while product–service system (PSS) innovation extends product value, increases material efficiency, and reduces waste generation. Achieving a successful transition requires active synergy among government, industry, society, and academia. Implications & Recommendations: Future research should focus on linking sustainability-driven innovation with circular practices in energy efficiency, high performance infrastructure, and governance systems designed for low carbon futures. Policymakers and practitioners must strengthen cross sector collaboration and innovation-oriented policy frameworks. Contribution & Value Added: This review consolidates and advances understanding of BMI pathways within circular and sustainable ecosystems, offering theoretical and practical insights to guide future research and implementation.